Plasma-aminothiols status and inverse correlation of total homocysteine with B-vitamins in arsenic exposed population of West Bengal, India. Issue 11 (18th September 2016) - Mukherjee, Ashit K.; Manna, Sujoy K.; Roy, Sanjit K.; Chakraborty, Manisha; Das, Surajit; Naskar, Jnan P.
ABSTRACT: Chronic arsenic toxicity is a serious environmental health problem across the world. Bangladesh and India (particularly the state of West Bengal) are the worst affected countries with such problem. The present study reports plasma-aminothiols (p-aminothiols) like L-cysteine (L-Cys), cysteinyl glycine (Cys-gly), total homocysteine (t-Hcy) and glutathione (GSH) status, and the inverse relationship of t-Hcy with B-vitamins (B1, B6, B9 and B12 ) in arsenic exposed population of West Bengal, India. Reverse phase HPLC was used to measure p-aminothiols and serum B-vitamins in different arsenic exposed population. Arsenic in drinking water and urine were measured by flow injection analysis system – Atomic Absorption Spectrometry (FIAS-AAS) and Transversely heated graphite atomizer (THGA-AAS) techniques, respectively. Water arsenic exposure was >50 µg/L in 50% population, of which majority (33.58%) belong to the range of >50–500 µg/L and more than 8% were even >1000 µg/L. Urine arsenic (µg/g creatinine) levels increased with arsenic exposure. The variability among p-aminothiols was also observed with higher exposure to arsenic in drinking water. A significant difference between exposed and control population was noticed for plasma L-Cys. The difference of B-vitamins between the population exposed to <50 and >50 µg/L arsenic in drinking water was also found to be significant. B9 and B12 deficiency with increased consumption of arsenic in water corroborates the anemic conditions commonly observed among arsenic exposed population. The aminothiol status indicated oxidative stress in exposed population. This study demonstrated progressive increase in plasma t-Hcy as well as inverse relationships of serum B-vitamins with increased water arsenic concentration.